Formation histories of stars, clusters, and globular clusters in the E-MOSAICS simulations - Reina-Campos, Marta; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. The formation histories of globular clusters (GCs) are a key diagnostic for understanding their relation to the evolution of the Universe through cos
Gesehen am 03.06.2019